Existence and Monotone Iteration of Positive Pseudosymmetric Solutions for a Third-Order Four-Point BVP with p-Laplacian. (3rd June 2013) - Li, Dan; Wang, Libo; Pei, Minghe
Abstract : We study the existence and monotone iteration of solutions for a third-order four-point boundary value problem with p -Laplacian. An existence result of positive, concave, and pseudosymmetric solutions and its monotone iterative scheme are established by using the monotone iterative technique. Meanwhile, as an application of our result, an example is given.